Proje finansmanında Türk hukukuna tabi teminatlar ve özellikle hesap rehni - Ustaoğlu, Funda (My University, 2019)
Tezimizde nakit akışı finansmanı olarak kabul edilen ve son on yıldır ülkemizde gerçekleştirilen yatırım projelerinde tercih edilen bir finansman modeli olan proje finansmanı perspektifinden Türk Hukukuna tabi teminatlar incelenmiştir. İncelemelerimiz sırasında Türk Hukukuna tabi teminatlara proje finansmanı perspektifinden yaklaşılmış ve teminatlara ilişkin özellik arz eden hususlar üzerinde durulmuştur. Çalışmamızda özellikle proje finansmanının doğasından kaynaklanan nedenlerle Türk Hukukuna tabi teminatlarda meydana gelen farklılıklar ve yabancı hukuk sistemlerinde kabul edilen ve proje finansmanı uygulaması ile hukukumuza yansıyan müesseselerin neden olduğu farklılıklar üzerinde durulmuştur. Türk Hukukuna tabi teminatlara ilişkin farklılıklara ve sorunlu hususlara hem teorik hem de pratik çözümler geliştirilmeye çalışılmış ve proje finansmanında geçerli bir teminat kurgusu oluşturulması için izlenmesi gereken yöntemler ve uygulanması gereken hukuki politikalar belirlenmeye çalışılmıştır.

In our thesis the securities subject to Turkish Law were examined with regard to project financing as a preferred financing model in the investments taking place in Turkey in the last decade in addition to being accepted as a cash flow financing. In the process of our examinations, we approached to the securities subject to Turkish Law from the point of project financing, and focused on the issues which are peculiar for securities. In our study, particularly due to reasons arising out of the project financing nature, the differences related to the securities subject to Turkish Law as well as the ones accepted in foreign legal systems and reflected unto Turkish Law by means of the project financing practice were emphasized. Both theoretical and practical solutions were worked out in relation with the differences and problematic issues of the securities subject to Turkish Law while the methods to be pursued and legal policies to be applied were studied.
Keywords: Civil law; Hukuk; Law; Medeni hukuk; Proje Finansmanı Teminat Project Finance Security; Turkey; Türkiye